2018
DOI: 10.3928/02793695-20180503-02
|View full text |Cite
|
Sign up to set email alerts
|

Violence Management in a Nigerian Psychiatric Facility: Psychiatric–Mental Health Nurses' Current Practices and Their Effectiveness

Abstract: Patient violence in mental health care settings is daunting and stressful, as well as increasingly burdensome for professionals in low/middle income countries, specifically Africa. Patient violence has contributed to increased work hazards for health care professionals and may lead to patients being sedated or restrained, potentially resulting in injury to either the patient or provider. The current study assessed Nigerian psychiatric-mental health nurses' current practices of violence management in a hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Staff believed managing assaults should not be part of their role and that different professionals such as security should manage them (Oyelade & Ayandiran, 2018). This led staff to question their professional identity:…”
Section: Theme 3: Expectations Of Riskmentioning
confidence: 99%
See 3 more Smart Citations
“…Staff believed managing assaults should not be part of their role and that different professionals such as security should manage them (Oyelade & Ayandiran, 2018). This led staff to question their professional identity:…”
Section: Theme 3: Expectations Of Riskmentioning
confidence: 99%
“…Staff believed that physically large patients could commit more serious assaults and required management from physically strong nursing staff (Oyelade & Ayandiran, 2018). Some studies reported that female staff were at a greater risk of aggression from male patients (Camuccio et al, 2012;Zuzelo et al, 2012), while in Wright et al (2014), staff reported that female staff had a 'calming influence'.…”
Section: Staff Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Health care profession has even more severe consequences from workplace violence which appears as a major issue globally important in terms of violence against nurses and other health professionals at their work place. This violence may include verbal abuse from patients and their relative, physical violence like hitting and beating, and sexual harassment etcetera (Oyelade & Ayandiran, 2018).The verbal violence has the highest occurrence of all work place violence. Moreover, Nurses are exposed to work place violence more than any other health care discipline because they remain in contact with patients and their families for all the times (Alameddine et al, 2015).…”
Section: Introductionmentioning
confidence: 99%